2013
DOI: 10.1016/j.heares.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin administration on the stapes footplate causes greater hearing loss and vestibulotoxicity than round window administration in guinea pigs

Abstract: Clinically, gentamicin has been used extensively to treat the debilitating symptoms of Mèniére’s disease and is well known for its vestibulotoxic properties. Until recently, it was widely accepted that the round window membrane (RWM) was the primary entry route into the inner ear following intratympanic drug administration. In the current study, gentamicin was delivered to either the RWM or the stapes footplate of guinea pigs (GPs) to assess the associated hearing loss and histopathology associated with each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 40 publications
0
29
0
2
Order By: Relevance
“…Different drugs had different results [15,16] . It was reported that application of gentamicin to oval window caused more vestibulotoxicity and hearing loss in Gunea pigs [17] . This was supposed to be due to more absorption of gentamicin through the oval window.…”
Section: Discussionmentioning
confidence: 98%
“…Different drugs had different results [15,16] . It was reported that application of gentamicin to oval window caused more vestibulotoxicity and hearing loss in Gunea pigs [17] . This was supposed to be due to more absorption of gentamicin through the oval window.…”
Section: Discussionmentioning
confidence: 98%
“…Also, inhibition of steroidogenesis by gentamicin might be due to increasing tumor necrosis factor alpha (TNF-α) gene expression as agreed by Zager et al [35] who demonstrated that TNF-α gene expression was doubled after gentamicin administration. The increased (TNF-α) gene inhibits steroidogenesis in Leydig cells at the transcriptional level of steroidogenic enzymes [36,37]. In rodents, Leydig cells synthesize oestrogen in adults; moreover, it has been shown that germ cells (especially spermatid) from adult male rat account for half of the testicular source of oestrogens through aromatization [38].…”
Section: Discussionmentioning
confidence: 99%
“…Within the middle ear, Lutrol F127 will not be in direct contact with the perilymph (with diffusion through round window membrane, and also the stapes as has recently been demonstrated by O'leary and co-workers). 29,30 Therefore, the concentration gradient will be lower and the dissolution of the polymer will be lower too. In addition, as the perilymph effectively does not flow, which is a very different situation to the rotating fluid on an orbital shaker, it is believed that the current system when injected in vivo could be more sustained.…”
Section: Discussionmentioning
confidence: 99%